Post-transplant allograft outcomes according to mismatch between donor kidney volume and body size of recipients with pre-transplant diabetes mellitus. (August 2021) - Park, Yohan; Lee, Hanbi; Eum, Sang Hun; Kim, Hyung Duk; Ko, Eun Jeong; Yang, Chul Woo; Chung, Byung Ha
Highlights: Allograft outcomes were worse in pre-transplant DM with relatively small kidney. Worse allograft outcomes are thought to be due to non-immunologic mechanisms. In ESKD patients with DM, the size of the donated kidney should also be considered. Abstract: Aims: The aim of this study was to investigate allograft outcomes when relatively small kidneys were donated to patients with pre-transplant diabetes mellitus (DM). Methods: From January 2010 to December 2018, 788 cases of non-sensitized living donor kidney transplant recipient and donor pairs were enrolled. The subjects were divided into four groups according to the relative size of kidney and pre-transplant DM status: non-DM large kidney, non-DM small kidney, DM large kidney, and DM small kidney. We compared allograft outcomes between these four groups. Results: The four groups did not show differences in the development of de novo donor-specific antibody and acute rejection. However, a significantly greater decline of allograft function and increased proteinuria were observed in the DM small kidney group. The highest death-censored graft loss rate (P = 0.008) was also observed in this group and the combination of relatively small kidney size and pre-transplant DM was an independent risk factor for death-censored graft loss. In addition, the relatively small kidney and pre-transplant DM showed significant interaction with each other. Conclusions: The size mismatch between donated kidney volume and recipient body size should be considered in donor selection of patients with pre-transplant DM.